Development of the new spectrophotometric method for determination of Chlordiazepoxide by ion-pair complex formation reaction - Zakaria, Safaa A.; Othman, Nabeel S. (Iraqi Journal of Science, 2026)
The study focuses on the development of a spectrophotometric method for quantifying chlordiazepoxide in its pure form and pharmaceutical formulation. The developed method is based on the formation of a colored ion-association complex through the reaction of chlordiazepoxide with Bengal rose B dye, facilitated by KH- phthalate buffer at pH 4.0. The effects of various factors on the formation of the complex were studied at 568 nm., in the concentration range of 3 to 30 µg. mL-1. The calibration curve exhibited linearity following Beer’s law, demonstrating molar absorptivity and Sandell’s sensitivity were 1.2771x104 L.mol-1.cm-1and 0.0234 μg∙cm-2 respectively. The detection limit was determined to be 0.0190 μg∙ml-1, while the quantitation limit reached 0.0633 μg∙ml-1. Investigation of the reaction stoichiometry revealed a 1:1 molar ratio between chlordiazepoxide and the dye. The standard addition method has been used to determine chlordiazepoxide drug quantity and ensure there were no interferences with pharmaceutical additives.